The First Clinical Use of Augmented Reality to Treat Salivary Stones. (10th July 2020) - Lysenko, Anna; Razumova, Alexandra; Yaremenko, Andrey; Mirzakhmedov, Rustam; Zubareva, Anna; Chibisova, Marina
Abstract : In this study, we report our first experience of applying the concretion visualization method using augmented reality technology. A clinical case of a new surgical intervention on the parotid salivary gland with the localization of salivary stone in its parenchyma is considered. During additional diagnostics, it was found that the size of the concretion exceeds 5 mm which did not allow us to use the endoscopic technologies. That was the reason for the choice of surgical intervention external access using salivary stone visualization with the help of augmented reality. The preoperative procedures included making the upper jaw cast model, fitting the model and individual mouthguard with an X-ray contrast marker and marker slot. In addition to this, computed tomography of the head and neck using a mouthguard was made. During surgery under general anesthesia with nasal intubation, the mouthguard together with the marker is installed in the patient's mouth and the surgeon puts on the glasses to visualize the stone image in place of its localization. This method enables to visualize the salivary stone on all surgery stages no matter what type of approach is used or performing hydropreparation. That is why using the augmented reality appears promising and is to be studied further.